PENERAPAN SIKLUS PDCA PADA PEMBIBITAN KELAPA SAWIT (Elaeis guineensis Jacq) DI PEMBIBITAN UTAMA PT PERKEBUNAN NUSANTARA IV REGIONAL III KECAMATAN BUKIT KAPUR KOTA DUMAI - Arman Maulana (Jurnal Sapta Agrica, 2026)
Oil palm (Elaeis guineensis Jacq.) is a strategic plantation commodity that contributes significantly to national foreign exchange earnings. The main nursery stage is a crucial phase in ensuring the availability of high-quality seedlings before field planting. This study aimed to examine the implementation of the PDCA (Plan, Do, Check, Action) cycle in improving the quality of oil palm seedlings, identify the challenges encountered, and formulate solutions to address these challenges at PT Perkebunan Nusantara IV Regional III, Bukit Kapur District, Dumai City. The study employed a descriptive qualitative approach, with data collected through interviews, field observations, and documentation studies. The results showed that the implementation of the PDCA cycle had been carried out systematically, with an activity implementation rate of 83.33%. The main challenges included delays in the procurement of production inputs, high rainfall, and labor shortages. The solutions implemented consisted of enhanced coordination, drainage improvement, and intensive supervision. The application of the PDCA cycle proved effective in improving operational efficiency and the quality of oil palm seedlings in the main nursery.